Phonetics As a Linguistic Discipline - Yuldasheva Farog’at Farkhadovna (Zien Journals, 2022)
Language, being a means of communication between people, serves to convey and perceive meaning. for these meanings to be perceived, their constituent units must have a material form. Language exists in two material forms - oral and written
Keywords: phonetics; sound; language; speech